Lymphangiogenesis and angiogenesis: concurrence and/or dependence? Studies in inbred mouse strains - Nakao, Shintaro (The Federation of American Societies for Experimental Biology, 2010)
Genetic background significantly affects angiogenesis in mice. However, lymphangiogenic response to growth factors (GFs) in different strains has not been studied. We report constitutive expression of corneal lymphatics that extends beyond the limits of normal limbal vessels. In untreated corneas, the total number (P=0.006), the number above blood vessels (P=10(−8)), and the area of preexisting lymphatics (P=0.007) were significantly higher in C57BL/6 than in BALB/c mice. Normal corneas of three other strains, the nu/nu, 129E, and Black Swiss mice, showed in most parameters intermediate phenotypes. FGF-2(−/−) mice showed significantly less preexisting lymphatics than control (P=0.009), which suggests a role for this GF in lymphatic development. VEGF-A-induced corneal lymphangiogenic response was significantly higher in BALB/c mice (P=0.03), but it did not differ significantly in C57BL/6 mice, when compared to PBS-implanted control. FGFR-3 expression was higher in C57BL/6 than BALB/c mice, which suggests GF-receptor heterogeneity as a possible explanation for strain-dependent differences. The heterogeneity of preexisting lymphatic vessels in the limbal area significantly correlated with the extent of corneal lymphangiogenesis (VEGF-A: r=0.7, P=0.01; FGF-2: r=0.96, P=10(−5)) in BALB/c but not in C57BL/6 mice. Removal of conjunctival lymphatics did not affect GF-induced lymphangiogenesis. This work introduces physiological expression of lymphatics without blood vessels, which indicates that angiogenesis and lymphangiogenesis, even though intricately related, may occur independently. Furthermore, we show strain-dependence of normal and GF-induced lymphangiogenesis. These differences may affect disease development in various strains.—Nakao, S., Maruyama, K., Zandi, S., Melhorn, M. I., Taher, M., Noda, K., Nusayr, E., Doetschman, T., Hafezi-Moghadam, A. Lymphangiogenesis and angiogenesis: concurrence and/or dependence? Studies in inbred mouse strains.